Download presentation

Presentation is loading. Please wait.

Published byRashad Rooke Modified over 2 years ago

1
USING DISTRIBUTIVE PROPERTY HIPPITY H0PPITY DISTRIBUTIVE PROPERTY Created by Pat Prewitt, Central HS, Beaumont, TX

2
This is the Easter Bunny He brings eggs to good boys and girls. Created by Pat Prewitt, Central HS, Beaumont, TX

3
This is the Distributive bunny He brings numbers to ( ) ( x + 3 ) = 8 (2) Created by Pat Prewitt, Central HS, Beaumont, TX

4
So now we have (2) x + (2)3 = 8 2x + 6 = 8 And we loose the other ( ) Multiply out Created by Pat Prewitt, Central HS, Beaumont, TX

5
Try another with distributive bunny ( 2x + 6 ) = 7 3 (3) Created by Pat Prewitt, Central HS, Beaumont, TX

6
And this gives us 3(2x) + 3(6) = 7 6x + 19 = 7 Remember—loose the other ( ) Created by Pat Prewitt, Central HS, Beaumont, TX

7
Try these on your own 1. 3 ( x + 4 ) = ( x – 3 ) = ( c + 1 ) = ( 8 + t ) = 22 Created by Pat Prewitt, Central HS, Beaumont, TX

8
Answers 1. 3x +12 = 21 x = x – 6 = 8 x = c + -2 = -4 c = t = 22 t = 3 Created by Pat Prewitt, Central HS, Beaumont, TX

9
( 3 + 5x ) + 5 = 18 5 (5) Remember: The bunny only give numbers to the ( ) Not in the ( ) no numbers for you. Created by Pat Prewitt, Central HS, Beaumont, TX

10
So now we have (5)3 + (5)5x + 5 = x + 5 = 18 Created by Pat Prewitt, Central HS, Beaumont, TX

11
Try these on your own 1. 3 ( 2x – 1) + 6 = ( x – 12 ) + 10 = x + 2 (5 – x ) = 12 Created by Pat Prewitt, Central HS, Beaumont, TX

12
Answers 1.6x – = -15 x = x – = 100 x = x + 10 – 2x = 12 x = 2 Created by Pat Prewitt, Central HS, Beaumont, TX

13
Let’s try a hard problem 3 ( x + 7) = 18 – (-2) Created by Pat Prewitt, Central HS, Beaumont, TX

14
So now we have 3 (-2) x + (-2) 7 = 18 3 – 2x = 18 Created by Pat Prewitt, Central HS, Beaumont, TX

15
Let’s try a harder problem 2 ( x + 7) = 10 – (-) Created by Pat Prewitt, Central HS, Beaumont, TX

16
So now we have 2 (-) x + (-) 7 = 10 2 –x + -7 = 10 2 – 7 – x = – x = 10 Created by Pat Prewitt, Central HS, Beaumont, TX

17
Try these 1. 2 – 3 ( x + 4) = – 5 (m – 1 ) = n – (3n + 4) = -6 Created by Pat Prewitt, Central HS, Beaumont, TX

18
Answers 1. 2 – 3 x – 12 = 17 x = – 5m + 5 = 111 m= n –3n – 4) = -6 n = Created by Pat Prewitt, Central HS, Beaumont, TX

Similar presentations

© 2016 SlidePlayer.com Inc.

All rights reserved.

Ads by Google